Mineralogy of Ga- and Ge-bearing metallurgical slags from Tsumeb, Namibia. (10th December 2021) - Ettler, Vojtěch; Mihaljevič, Martin; Strnad, Ladislav; Jedlicka, Radim; Kříbek, Bohdan; Bowell, Rob J.; Kamona, Fred; Mapani, Ben
Abstract: Gallium (Ga) and germanium (Ge) are technologically important critical elements. Lead blast furnace slags from Tsumeb, Namibia, comprise over two million metric tons of material that contains high levels of Ga (135–156 ppm) and Ge (128–441 ppm) in addition to significant Zn concentrations (up to 11 wt.%) and represent a potential resource for these elements. A combination of mineralogical and chemical methods (PXRD, FEG-SEM-EPMA and LA-ICP-MS) indicated different partitioning of Ga and Ge within the individual slag phases. Gallium is predominantly bound in small euhedral crystals of Zn–Fe–Al spinels (<10 μm in size), exhibiting concentrations in the range of 480–1370 ppm (up to 0.004 atoms per formula unit, apfu). Concentrations of Ga in other phases (e.g. melilite) are systematically below 90 ppm. The principal host of Ge is the silicate glass and, to a lesser extent, silicates (melilite and olivine group phases). Concentrations of Ge in glass attained a concentration of 470 ppm (EPMA), but the LA-ICP-MS analysis of glass matrix containing submicrometre spinel crystallites indicated that average Ge levels vary in the range of 113–394 ppm. In the potential extraction of Ga and Ge, the results indicate that ultrafine milling is needed to liberate the Ga- and Ge-hosting phases prior to metallurgical processing of the slag.